Independent constitutive expression of the aerobic and anaerobic pathways of glycerol catabolism in Klebsiella aerogenes. - Ruch, F E (1975)
Klebsiella aerogenes dissimilates glycerol aerobically via an inducible pathway initiated by an adenosine triphosphate-linked kinase that converts the substrate to sn-glycerol 3-phosphate. Phosphorylated glycerol is then dehydrogenated to dihydroxyacetone phosphate by an enzyme characteristic of a flavoprotein. Anaerobically, the organism dissimilates glycerol via an inducible pathway initiated by a nicotinamide adenine dinucleotide-linked dehydrogenase that converts the substrate to dihydroxyacetone. The keto product is then phosphorylated by another adenosine triphosphate-linked kinase. Two kinds of constitutive mutants have been isolated: one affecting the aerobic and the other the anaerobic pathway.